Implementing Content and Language Integrated Learning (CLIL) Through Group Discussion in Reading Comprehension Class - Zunaedi, Balqis Nazilah Husna; Frida Unsiah,; Khairil Azwar Razali, (Journal of Language and Literature Studies, 2024)
Utilizing CLIL through group discussions has significantly enhanced the learning experience in accounting. To achieve this, CLIL is frequently integrated into reading comprehension classes to directly gather responses from international accounting program students through group discussions, aiding in managing and monitoring student engagement and comprehension. The study aimed to explore students' perspectives on the utilization of CLIL through group discussions. Six students from the international accounting program participated in a reading comprehension session employing the CLIL method through group discussions. Researchers conducted interviews to assess students' views regarding the expectations, benefits, and drawbacks of utilizing CLIL through group discussions. Findings revealed that participants perceived several advantages of using CLIL through group discussions, including improved comprehension of the material, opportunities for students to exchange their understanding, and increased motivation. However, challenges such as students' limited English fluency leading to prolonged discussions and potential misunderstandings of the material were noted. It is suggested that CLIL through group discussions be considered as an effective technique for enhancing reading comprehension.